IDNLearn.com: Your trusted platform for finding precise and reliable answers. Find in-depth and trustworthy answers to all your questions from our experienced community members.
Sagot :
Sure! Let me guide you through each problem step-by-step:
### Problem 1: [tex]\(4 \frac{1}{2} - 5 \frac{1}{4}\)[/tex]
1. Convert mixed numbers to improper fractions:
- [tex]\(4 \frac{1}{2} = 4 + \frac{1}{2} = \frac{8}{2} + \frac{1}{2} = \frac{9}{2}\)[/tex]
- [tex]\(5 \frac{1}{4} = 5 + \frac{1}{4} = \frac{20}{4} + \frac{1}{4} = \frac{21}{4}\)[/tex]
2. Find a common denominator and subtract:
- [tex]\(\frac{9}{2} = \frac{18}{4}\)[/tex]
Then, [tex]\(\frac{18}{4} - \frac{21}{4} = \frac{18 - 21}{4} = -\frac{3}{4}\)[/tex]
So, [tex]\(4 \frac{1}{2} - 5 \frac{1}{4} = -\frac{3}{4} = -0.75\)[/tex]
### Problem 2: [tex]\(2 \cdot 5 \frac{2}{3} - 3 \frac{1}{6}\)[/tex]
1. Convert mixed numbers to improper fractions:
- [tex]\(5 \frac{2}{3} = 5 + \frac{2}{3} = \frac{15}{3} + \frac{2}{3} = \frac{17}{3}\)[/tex]
- [tex]\(3 \frac{1}{6} = 3 + \frac{1}{6} = \frac{18}{6} + \frac{1}{6} = \frac{19}{6}\)[/tex]
2. Multiply and then subtract:
- [tex]\(2 \cdot \frac{17}{3} = \frac{34}{3}\)[/tex]
Then, find a common denominator for subtraction:
- [tex]\(\frac{34}{3} = \frac{68}{6}\)[/tex]
Then, [tex]\(\frac{68}{6} - \frac{19}{6} = \frac{68 - 19}{6} = \frac{49}{6}\)[/tex]
3. Convert back to a mixed number:
- [tex]\(\frac{49}{6} = 8 \frac{1}{6}\)[/tex]
So, [tex]\(2 \cdot 5 \frac{2}{3} - 3 \frac{1}{6} = 8 \frac{1}{6} \approx 8.166666666666668\)[/tex]
### Problem 3: [tex]\(3 \frac{6}{9} - 2 \frac{1}{3}\)[/tex]
1. Simplify fractions:
- [tex]\(3 \frac{6}{9} = 3 + \frac{6}{9} = 3 + \frac{2}{3}\)[/tex]
2. Convert the mixed numbers:
- [tex]\(3 \frac{2}{3} = \frac{9}{3} + \frac{2}{3} = \frac{11}{3}\)[/tex]
- [tex]\(2 \frac{1}{3} = 2 + \frac{1}{3} = \frac{6}{3} + \frac{1}{3} = \frac{7}{3}\)[/tex]
3. Subtract:
- [tex]\(\frac{11}{3} - \frac{7}{3} = \frac{11 - 7}{3} = \frac{4}{3}\)[/tex]
4. Convert back to a mixed number:
- [tex]\(\frac{4}{3} = 1 \frac{1}{3}\)[/tex]
So, [tex]\(3 \frac{6}{9} - 2 \frac{1}{3} = 1 \frac{1}{3} = 1.333333333333333\)[/tex]
### Problem 4: [tex]\(3 \frac{1}{2} - 2 \frac{1}{3}\)[/tex]
1. Convert mixed numbers to improper fractions:
- [tex]\(3 \frac{1}{2} = 3 + \frac{1}{2} = \frac{6}{2} + \frac{1}{2} = \frac{7}{2}\)[/tex]
- [tex]\(2 \frac{1}{3} = 2 + \frac{1}{3} = \frac{6}{3} + \frac{1}{3} = \frac{7}{3}\)[/tex]
2. Find a common denominator and subtract:
- [tex]\(\frac{7}{2} = \frac{21}{6}\)[/tex]
- [tex]\(\frac{7}{3} = \frac{14}{6}\)[/tex]
Then, [tex]\( \frac{21}{6} - \frac{14}{6} = \frac{7}{6}\)[/tex]
3. Convert back to a mixed number:
- [tex]\(\frac{7}{6} = 1 \frac{1}{6} \approx 1.1666666666666665\)[/tex]
So, [tex]\(3 \frac{1}{2} - 2 \frac{1}{3} = 1 \frac{1}{6} \approx 1.1666666666666665\)[/tex]
### Problem 5: [tex]\(4 \frac{3}{4} - 2 \frac{2}{5}\)[/tex]
1. Convert mixed numbers to improper fractions:
- [tex]\(4 \frac{3}{4} = 4 + \frac{3}{4} = \frac{16}{4} + \frac{3}{4} = \frac{19}{4}\)[/tex]
- [tex]\(2 \frac{2}{5} = 2 + \frac{2}{5} = \frac{10}{5} + \frac{2}{5} = \frac{12}{5}\)[/tex]
2. Find a common denominator and subtract:
- [tex]\(\frac{19}{4}\)[/tex] and [tex]\(\frac{12}{5}\)[/tex] common denominator is 20:
- [tex]\(\frac{19}{4} = \frac{95}{20}\)[/tex]
- [tex]\(\frac{12}{5} = \frac{48}{20}\)[/tex]
Then, [tex]\(\frac{95}{20} - \frac{48}{20} = \frac{95 - 48}{20} = \frac{47}{20}\)[/tex]
3. Convert back to a mixed number:
- [tex]\(\frac{47}{20} = 2 \frac{7}{20}\)[/tex]
So, [tex]\(4 \frac{3}{4} - 2 \frac{2}{5} = 2 \frac{7}{20} \approx 2.35\)[/tex]
### Problem 1: [tex]\(4 \frac{1}{2} - 5 \frac{1}{4}\)[/tex]
1. Convert mixed numbers to improper fractions:
- [tex]\(4 \frac{1}{2} = 4 + \frac{1}{2} = \frac{8}{2} + \frac{1}{2} = \frac{9}{2}\)[/tex]
- [tex]\(5 \frac{1}{4} = 5 + \frac{1}{4} = \frac{20}{4} + \frac{1}{4} = \frac{21}{4}\)[/tex]
2. Find a common denominator and subtract:
- [tex]\(\frac{9}{2} = \frac{18}{4}\)[/tex]
Then, [tex]\(\frac{18}{4} - \frac{21}{4} = \frac{18 - 21}{4} = -\frac{3}{4}\)[/tex]
So, [tex]\(4 \frac{1}{2} - 5 \frac{1}{4} = -\frac{3}{4} = -0.75\)[/tex]
### Problem 2: [tex]\(2 \cdot 5 \frac{2}{3} - 3 \frac{1}{6}\)[/tex]
1. Convert mixed numbers to improper fractions:
- [tex]\(5 \frac{2}{3} = 5 + \frac{2}{3} = \frac{15}{3} + \frac{2}{3} = \frac{17}{3}\)[/tex]
- [tex]\(3 \frac{1}{6} = 3 + \frac{1}{6} = \frac{18}{6} + \frac{1}{6} = \frac{19}{6}\)[/tex]
2. Multiply and then subtract:
- [tex]\(2 \cdot \frac{17}{3} = \frac{34}{3}\)[/tex]
Then, find a common denominator for subtraction:
- [tex]\(\frac{34}{3} = \frac{68}{6}\)[/tex]
Then, [tex]\(\frac{68}{6} - \frac{19}{6} = \frac{68 - 19}{6} = \frac{49}{6}\)[/tex]
3. Convert back to a mixed number:
- [tex]\(\frac{49}{6} = 8 \frac{1}{6}\)[/tex]
So, [tex]\(2 \cdot 5 \frac{2}{3} - 3 \frac{1}{6} = 8 \frac{1}{6} \approx 8.166666666666668\)[/tex]
### Problem 3: [tex]\(3 \frac{6}{9} - 2 \frac{1}{3}\)[/tex]
1. Simplify fractions:
- [tex]\(3 \frac{6}{9} = 3 + \frac{6}{9} = 3 + \frac{2}{3}\)[/tex]
2. Convert the mixed numbers:
- [tex]\(3 \frac{2}{3} = \frac{9}{3} + \frac{2}{3} = \frac{11}{3}\)[/tex]
- [tex]\(2 \frac{1}{3} = 2 + \frac{1}{3} = \frac{6}{3} + \frac{1}{3} = \frac{7}{3}\)[/tex]
3. Subtract:
- [tex]\(\frac{11}{3} - \frac{7}{3} = \frac{11 - 7}{3} = \frac{4}{3}\)[/tex]
4. Convert back to a mixed number:
- [tex]\(\frac{4}{3} = 1 \frac{1}{3}\)[/tex]
So, [tex]\(3 \frac{6}{9} - 2 \frac{1}{3} = 1 \frac{1}{3} = 1.333333333333333\)[/tex]
### Problem 4: [tex]\(3 \frac{1}{2} - 2 \frac{1}{3}\)[/tex]
1. Convert mixed numbers to improper fractions:
- [tex]\(3 \frac{1}{2} = 3 + \frac{1}{2} = \frac{6}{2} + \frac{1}{2} = \frac{7}{2}\)[/tex]
- [tex]\(2 \frac{1}{3} = 2 + \frac{1}{3} = \frac{6}{3} + \frac{1}{3} = \frac{7}{3}\)[/tex]
2. Find a common denominator and subtract:
- [tex]\(\frac{7}{2} = \frac{21}{6}\)[/tex]
- [tex]\(\frac{7}{3} = \frac{14}{6}\)[/tex]
Then, [tex]\( \frac{21}{6} - \frac{14}{6} = \frac{7}{6}\)[/tex]
3. Convert back to a mixed number:
- [tex]\(\frac{7}{6} = 1 \frac{1}{6} \approx 1.1666666666666665\)[/tex]
So, [tex]\(3 \frac{1}{2} - 2 \frac{1}{3} = 1 \frac{1}{6} \approx 1.1666666666666665\)[/tex]
### Problem 5: [tex]\(4 \frac{3}{4} - 2 \frac{2}{5}\)[/tex]
1. Convert mixed numbers to improper fractions:
- [tex]\(4 \frac{3}{4} = 4 + \frac{3}{4} = \frac{16}{4} + \frac{3}{4} = \frac{19}{4}\)[/tex]
- [tex]\(2 \frac{2}{5} = 2 + \frac{2}{5} = \frac{10}{5} + \frac{2}{5} = \frac{12}{5}\)[/tex]
2. Find a common denominator and subtract:
- [tex]\(\frac{19}{4}\)[/tex] and [tex]\(\frac{12}{5}\)[/tex] common denominator is 20:
- [tex]\(\frac{19}{4} = \frac{95}{20}\)[/tex]
- [tex]\(\frac{12}{5} = \frac{48}{20}\)[/tex]
Then, [tex]\(\frac{95}{20} - \frac{48}{20} = \frac{95 - 48}{20} = \frac{47}{20}\)[/tex]
3. Convert back to a mixed number:
- [tex]\(\frac{47}{20} = 2 \frac{7}{20}\)[/tex]
So, [tex]\(4 \frac{3}{4} - 2 \frac{2}{5} = 2 \frac{7}{20} \approx 2.35\)[/tex]
Thank you for joining our conversation. Don't hesitate to return anytime to find answers to your questions. Let's continue sharing knowledge and experiences! Thank you for visiting IDNLearn.com. We’re here to provide accurate and reliable answers, so visit us again soon.